HIGHER EDUCATION EVALUATION IN GERMANY - Ponomarenko., N. (Continuing Professional Education: Theory and Practice, 2023)
The article deals with the problem of higher education evaluation in Germany which is an important component of this type of education. The principles of evaluation in the field of higher education have been defined and characterised and are as follow: discursiveness, diversity of perspectives and process-orientation. The key stages of evaluation in a higher educational institution have been highlighted and described, in particular, self- evaluation, external evaluation and applying the results of the external and internal evaluation to practice. The differences in such notions as “ evaluation “ and “accreditation” have also been identified. Though evaluation and accreditation have the same methods and assessment criteria, their goals are different. evaluation is focused on quality improvement in higher education and enables to develop a strategy to achieve that goal, while accreditation simply indicates compliance with the minimum standards and requirements at the time of inspection. In addition to that, it has been found that accreditation is conducted on the basis of evaluation results. The article also describes the activity of German accreditation agencies and accreditation types which are programme, cluster, institutional and systematic ones. It has been found that one of the areas of evaluation in German higher education is ranking of higher educational institutions. Moreover, the research offers the analysis of the ranking system, which is adopted by The Centre of Development of Higher Educational Institutions in Germany, and gives characteristics to opportunities and educational conditions related to academic subjects and research activities conditions as well as assesses bachelor courses in the light of graduates’ further employment opportunities.